Selective balloon‐occluded transarterial chemoembolization for patients with one or two hepatocellular carcinoma nodules: Retrospective comparison with conventional super‐selective TACE. Issue 2 (2nd September 2015) - Irie, Toshiyuki; Kuramochi, Masashi; Kamoshida, Toshiro; Takahashi, Nobuyuki
Abstract : Aim: Selective balloon‐occluded transarterial chemoembolization (B‐TACE) enables strong TACE; infusion of more volume of lipiodol emulsion and forceful injection of embolization materials. The aim of this study is to analyze the efficacy of B‐TACE for patients with one or two hepatocellular carcinoma (HCC) nodules compared with conventional super‐selective TACE using a microcatheter (C‐TACE). Methods: We retrospectively selected patients without previous history of TACE, with one or two HCC nodules, with performance status 0/1, and with liver function of Child–Pugh score A/B. Between 2008 and 2010, a 3‐Fr microballoon catheter was used for targeted TACE (B‐TACE group). Between 2005 and 2008, a 2‐Fr microcatheter was used (C‐TACE group). Control rates of primary nodule, overall survival rates and tumor‐free rates in the liver were calculated for each group using the Kaplan–Meier method. Univariate analysis was performed to compare between the groups using the log–rank test. Multivariate analysis was performed for analysis of prognostic factors using Cox's proportional hazard model. The factors were B‐TACE versus C‐TACE, Child–Pugh score A versus B, single nodule versus double, large nodule versus small, elder versus not, and prior radiofrequency ablation treatment versus not. Results: Control rates of the primary nodule were improved by B‐TACE. B‐TACE was an independent factor to improve both control rates of the primary nodule and overall survival rates. Child–Pugh score A was an independent factor to increase overall survival rates. There was no statistically significant difference in overall survival or tumor‐free survival rates between the groups. Conclusion: B‐TACE was an independent factor to improve overall survival rates on multivariate analysis, but there was no significant difference in overall survival rates between B‐TACE and C‐TACE groups on univariate analysis.